Εκφοβισμός/θυματοποίηση στο σχολικό πλαίσιο και μοναξιά - Γαλανάκη, Ε.; Π Βογιατζόγλου (Παιδαγωγική Επιθεώρηση, 2007)
This theoretical study presents an overview of the links between bullying / victimization and loneliness during childhood. Bullying and victimization are conceptually clarified and research evidence is briefly reviewed about bullying and victimization as risk factors for children's mental health. Next, this study focuses on the links between bullying / victimization and loneliness mainly in the school context. Complex paths leading from bullying / victimization to loneliness and vice versa, and developmental trajectories of this association emerged from the existing concurrent and longitudinal data. Finally, some research implications for prevention and intervention efforts aiming at reducing bullying in school are discussed.